Linking education and criminology research to understand the schooling experiences of gang youth and adults - Huerta, Adrian H. (The Oxford handbook of gangs and society, 2024)
This chapter centers on the influence of schools and schooling practices related to gang-associated populations in primary, secondary, and postsecondary education. Drawing from scholarship in education, criminology, and related fields helps to illuminate how school-based practices are informed by the school-to-prison pipelines that negatively impact gang-involved youth. Harmful school practices contribute to the social and educational marginalization of young people affected and involved in gangs and help to explain the significant educational disparities in high school completion and college enrollment for gang-associated populations. Throughout the chapter quotes are embedded from former gang members to show how they overcame mistreatment throughout the educational pipeline, reframing gang-associated youth to being at-promise rather than at-risk.